Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.7759/cureus.5714
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Enteropathy-associated T-cell Lymphoma Type 2 with Pulmonary Metastasis

Abstract: Herein, we present a very rare case of enteropathy-associated T-cell lymphoma (EATL) type 2 with pulmonary metastasis which was biopsy-proven. This is a very rare type of lymphoma, and no case reports or studies of enteropathy-associated T-cell lymphoma with pulmonary metastatic disease were found in the literature review.This 64-year-old male, who presented with an acute abdomen, was found to have a perforation. Subsequent pathology of the resected specimen showed neoplastic cells consistent with EATL type 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…ITLs mainly involve in the small intestine and colon; but in the advanced stage, they also involve in other extranodal sites, such as the stomach, skin, and brain [ 2 ]. Only two cases of MEITL with lung involvement have been reported [ 3 , 4 ]. The International Peripheral T-Cell Lymphoma Project reported that about 5% of 62 cases of EATL show lung involvement; however, they did not describe the details of any cases [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ITLs mainly involve in the small intestine and colon; but in the advanced stage, they also involve in other extranodal sites, such as the stomach, skin, and brain [ 2 ]. Only two cases of MEITL with lung involvement have been reported [ 3 , 4 ]. The International Peripheral T-Cell Lymphoma Project reported that about 5% of 62 cases of EATL show lung involvement; however, they did not describe the details of any cases [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…PET-CT showed multiple pulmonary nodules accompanied by the accumulation of fluorodeoxyglucose. He died owing to recurrence of perforation of the small intestine after one course of CHOP chemotherapy [ 3 ]. Suzuki et al reported the case of a 74-year-old male diagnosed as having MEITL with small intestine, lung, and brain involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Type II cells have medium size and relatively single morphology and more common in the Asian population. [3,34] Although the 2 diseases share many common clinical and pathological features, they have their own characteristics in terms of epidemiology, histology, immunophenotype and genetic characteristics. The WHO classification scheme of 2017 recognizes 4 subtypes of intestinal T-cell lymphoma: enteropathy-associated T-cell lymphoma, monomorphic epitheliotropic intestinal T-cell lymphoma, intestinal T-cell lymphoma, not otherwise specified, and indolent T-cell lymphoproliferative disorder of the GI tract (provisional).…”
Section: Discussionmentioning
confidence: 99%
“…MEITL is often associated with necrosis ( 7 ). To date, there has only been one report of a case of MEITL (EATL type 2) involving the lung, in which chest CT demonstrated multiple nodules without cavitation ( 8 ). In the present case, the chest CT findings demonstrated multiple nodules with cavitation in the bilateral lungs, which were compatible with lymphoma, and suggested necrotic lesions.…”
Section: Discussionmentioning
confidence: 99%